Identifikasi Keterdapatan Mineral Radioaktif pada Granit Muncung Sebagai Tahap Awal untuk Penilaian Prospek Uranium dan Thorium di Pulau Singkep - Ngadenin, Ngadenin; Karunianto, Adhika Junara (BRIN Publishing, 2016)
Singkep Island is part of Southeast Asia tin belt, which is one of the lithologies, composed of granite Muncung. Existence of granite allows formed deposits of radioactive minerals that prospect of the uranium and thorium. This research goal is to identify radioactive minerals occurrences on granit Muncung in the initial stage for prospect assessment of uranium and thorium in Singkep Island. The Methodologies are granite sampling, petrography analysis of Muncung granite samples, uranium and thorium content analysis and grain size analysis of pan concentrate samples. Radioactive minerals in Muncung granite are monazite and zircon, while in pan concentrate they are monazite, zircon, and xenotime. The percentage of monazite, zircon, and xenotime in the pan concentrate are 1.1–59.53 %, 0.68–55.07 %, and 0.3–3.54 % respectively. The uranium and thorium content in the pan concentrate are 30–1,346 ppm and 557–13,200 ppm respectively. It concluded that the area around the Muncung granite considered prospect for uranium and thorium, and possibly developed into more detailed exploration stage.